Airway Problems in Neonates—A Review of the Current Investigation and Management Strategies - Mok, Quen (Frontiers in Pediatrics, 2017)
Airway problems in the neonatal population are often life threatening, and raise challenging issues in diagnosis and management. The airway problems can result from congenital or acquired lesions and can be broadly classified into those causing obstruction or those due to an abnormal ‘communication’ in the airway. Many different investigations are now available to identify the diagnosis and quantify the severity of the problem, and these tests can be simple or invasive. Bronchography and bronchoscopy are essential to determine the extent and severity of the airway problem and to plan treatment strategy. Further imaging techniques help to delineate other commonly associated abnormalities. Echocardiography is also important to confirm any associated cardiac abnormality. In this review the merits and disadvantages of the various investigations now available to the clinician will be discussed. The current therapeutic strategies are discussed, and the review will focus on the most challenging conditions that cause the biggest management conundrums, specifically laryngo- tracheal cleft, congenital tracheal stenosis and tracheobronchomalacia. Management of acquired stenosis secondary to airway injury from endotracheal intubation will also be discussed as this is a common problem. Slide tracheoplasty is the preferred surgical option for long segment tracheal stenosis and results have improved significantly. Stents are occasionally required for residual or recurrent stenosis following surgical repair. There is sufficient evidence that a multidisciplinary team approach for managing complex airway issues provides the best results for the patient. There is ongoing progress in the field with newer diagnostic tools as well as development of innovative management techniques, such as biodegradable stents and stem cell based tracheal transplants, leading to a much better prognosis for these children in the future.